Atomic-Level Investigation of Reactant Recognition Mechanism and Thermodynamic Property in Glucosamine 6-Phosphate Deaminase Catalysis - Zhang, Xiao; Liu, Xiaoyuan; Zhang, Zhiyang; Zhao, Yuan; Wang, Chaojie (Frontiers in Chemistry, 2021)
Glucosamine 6-phosphate deaminase (NagB) influences the direction of N-acetylglucosamine (GlcNAc) metabolism, facilitating the conversion of D-glucosamine 6-phosphate (GlcN6P) to D-fructose 6-phosphate (Fru6P) with the release of ammonia. Here, extensive molecular dynamics simulations combined with various techniques were performed to study the recognition and delivery process of GlcN6P by SmuNagB, due to its guidance of subsequent enzymatic reaction. The key residues Lys194, His130, Arg127, Thr38, and Ser37 stabilize GlcN6P in the active site by hydrogen bond interactions, therein electrostatic and polar solvent effects provide the primary traction. Four delivery channels were identified, with GlcN6P most likely to enter the active site of NagB through a “door” comprising residues 6-10, 122-136, and 222-233. The corresponding mechanism and thermodynamic properties were investigated. An exothermic recognition and delivery process were detected, accompanied by the flipping of GlcN6P and changes in key direct and indirect hydrogen bond interactions, which provide the driving force for the chemical reaction to occur. Furthermore, “the lid motif” was identified that remain open in alkaline condition with different extent of opening at each stage of transfer that induced GlcN6P to move the active site of NagB. The work will assist in the elucidation of the catalytic mechanism of action of NagB, allowing inhibitors to be designed with superior dynamic behavior.